Kemampuan Guru Menyusun Soal HOTS dalam Bentuk Pilihan Ganda di SDN 02 Legokgunung - Ri Sumarni (Action Research Journal, 2022)
Composing HOTS questions is an ability that must be mastered by teachers to realize 21st century learning. This encourages researchers to examine how teachers are able to arrange HOTS questions in multiple choice form at SDN 02 Legokgunung. This study aims to provide an overview of the teacher's ability in compiling HOTS questions in the form of multiple choice at SDN 02 Legokgunung. This research method is descriptive percentage with the research subjects being teachers in grades I, II, III, IV, V and VI at SDN 02 Legokgunung. The data collection technique was obtained by documentation and analyzed by qualitative descriptive. The results showed that of the 6 class teachers, 1 person was in the poor category, namely the third grade teacher with a percentage of 70.28%, 2 sufficient categories, namely the second grade teacher with a percentage of 78.01%, 2 teachers in the good category, namely the first grade teacher with a percentage of 82 .50% and the fourth grade teacher with a percentage of 89.35%, and 1 teacher in the very good category, namely the sixth grade teacher with a percentage of 91.44%. From the material aspect, the teacher's ability to compose HOTS questions in the form of multiple choice is still lacking. This is indicated by the average percentage obtained is 63.47%, % of good construction aspects the average percentage is 85.37 . The average percentage of language aspects obtained is 96.11 very good categories. The average percentage of all aspects of 81.65% is included in the good category.